Penegakkan Hukum di Negara Republik Indonesia - Okky Irawan; Saverius Nahat; Tetty Nababan; Syafrida Syafrida; Sufiarina Sufiarina (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Law enforcement serves as a fundamental mechanism for establishing order, security, and peace within society. It encompasses efforts to prevent or eliminate violations of the law, addressing issues both preventively and repressively. However, challenges arise when actions taken do not align with established procedures. The appropriate course of action within a legal framework is essential, and when discussing legal protection in the context of procedural law, it is important to clarify that such protection should not be interpreted as a means to shield offenders from accountability. This study seeks to evaluate law enforcement in Indonesia through the lenses of legal certainty, justice, and societal benefit. Employing a literature review methodology, which relies on expert opinions, the findings indicate notable deficiencies in the law enforcement system in Indonesia. For an extended period, those seeking justice within society have yearned for equitable law enforcement. Nevertheless, current practices in law enforcement tend to prioritize legal certainty over the community's sense of justice. Various court decisions, for example in the case of grandmother Minah and Aal, the sandal thief, seem to illustrate that law enforcement tends towards the view that law is law and has given rise to public disappointment with law enforcement in Indonesia.